Depression is one of the most common psychological disorders that comorbids with substance use disorders. - Mehdi Amiri (Drug Control Headquarters, Research and Education Office, 2009)
introduction: Depression is one of the most common psychological disorders that comorbids with substance use disorders. depression is not only the factor that predisposes persons to abuse substanses but also the factor resulting in relapse. The aim of this study was to determine effectiveness of group behavioral activation treatment in reducing depressive symptoms and effects of this treatment in increasing mental health and quality of life in clients of therapeutic community. Method: 21 clients suffering depressive symptoms, randomly assigned to two groups: experimental group (n=10) and control group (n=11). The experimental group was treated by 8 sessions of group behavioral activation treatment. Depressive symptoms, mental health, and quality of life were assessed before and after treatment sessions in both groups. Results: decreasing of depressive symptoms and increasing of mental health in experimental group were significantly more than control group, but there was no significant difference between two groups in increasing quality of life. Conclusion: The effectiveness of a brief and pure behavioral group therapy in reducing depressive symptoms and increasing of mental health has important theoretical and practical implications. Applying pure behavioral methods to help treating and rehabilitating of patients with substance abuse is of great importance.